(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
India has growthprospect for retail industry with a huge number of consumers and other favorablefactors. But India’s retail market remains largely off-limits to largeinternational retailers like Wal-Mart, Tesco and Carrefour. Opposition toliberalizing FDI in this sector raises concerns about employment losses, unfaircompetition resulting in large-scale exit of incumbent domestic retailers andinfant industry arguments to protect the organized domestic retail sector thatis at a nascent stage. In 2012 the Indian Government approved proposal of 100percent FDI in retailing in India subject to certain conditions. Though thisproposal is being hailed by global retail giants, which until now have been involved in only wholesale cash and carry distribution in India and have been longing forentry into the Indian retail market for years. The proposal has received vehement opposition from a spectrum ofpolitical parties in India, many of them urging for a reversal of the proposal.As a result, the Indian government has stalled the implementation of this proposal which has temporarily washed off the wishes of the global retail players awaiting a bite of the Indian retail market. This paper attempts to studythe present status of FDI in retailing sector in India and the impacts of FDIon various concerned segments.